Their own agenda: The history, development, and culture of women's orchestras outside the united states - Alger, Bonnie Eve (Université du Maryland, 2018)
Women have been active as performers of instrumental music since the Medieval period, and yet their contributions are often overlooked. This dissertation examines the history of women’s orchestras outside the United States, and explores their development, as well as reasons for existing. Several factors regarding their development are taken into consideration, including time period, country, and culture in which the ensemble is present. The birth of the women’s orchestra is traced from the ospedali of the 18th century Venice to today. All-female ensembles from England, Canada, Cuba, and Afghanistan are profiled, as well as the Women’s Orchestra in Auschwitz. Two modern-day women’s orchestras – the Allegra Chamber Orchestra in Vancouver, British Columbia, and my recital orchestra at the University of Maryland – were surveyed in an attempt to learn more about the culture of women’s orchestras. This paper seeks to answer the questions “What is the culture of women's orchestras today, and should they continue to exist?”
Keywords: 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; DIG; approches et analyses; arts; discipline; femmes* musiciennes; genre; histoire des femmes*; histoire et politique; inégalités; musique; mémoires/thèses; périodes historiques; ressource en ligne; systèmes d'oppressions; thématiques

Art and sexual politics: women's liberation, women artists, and art history. - Hess, Thomas B.; Baker, Elizabeth C.; Hess, Thomas B.; Baker, Elizabeth C. (Art news series, 1978)
The growing momentum of the women's liberation movement has stirred controversy and self-examination in all areas of contemporary endeavor—education, business, sciences, politics and the arts. This superb collection of timely, thought-provoking essays provides a rich, multidimensional, view of the prejudices, historical distortions, and inadequacies inherent in the art establishment. The contributors present a harmonious plea for a sincere and unqualified acceptance of women artists in teh contemporary art world.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; justice sociale; moyen-âge; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques